PERAN KPU KOTA SURAKARTA DALAM MENINGKATKAN PARTISIPASI PEMILIH PEMULA PADA PEMILU SERENTAK TAHUN 2019 - Wijayanti, Sisworini Karya (Solidaritas, 2020)
This study aims to analyze the Role of KPU in Surakarta City Election in order to Improve the Participation of Beginner Voters in 2019 Concurrent Elections. This type of research is a qualitative descriptive with case study method. Data collection techniques used are:(1) Field Study,(2) Documentation. In order to know the role of the Surakarta City KPU in this study the authors used 4 theoretical indicators resulting from a comparison between Gede Diva and Munir consisting of:(1) regulator,(2) catalyst,(3) coordinator,(4) Facilitator.The results of this study as a whole are said to be successful which can be demonstrated by the following results: (1) Activities related to elections are in accordance with existing policies seen from the role of the regulator,(2) Information provided to the KPU to the first time voters about elections can be accepted and understood by novice voters according to the role of the catalyst (3) The relationship or cooperation between the KPU and the Election Supervisory Body,democracy heroes,the community,schools,campuses,media colleagues (journalists) are well established in accordance with the role of the coordinator,(4) Complete facilities that support socialization activities and political education are in accordance with the role of the facilitator. Keywords: Role, Participation, Simultaneous Election, Beginner Voters.